Mass spectrometry imaging of the capsaicin localization in the capsicum fruits - Taira, Shu; Shimma, Shuichi; Osaka, Issey; Kaneko, Daisaku; Ichiyanagi, Yuko; Ikeda, Ryuzo; Konishi-Kawamura, Yasuko; Zhu, Shu; Tsuneyama, Koichi; Komatsu, Katsuko (International Journal of Biotechnology for Wellness Industries, 2012)
We succeeded in performing mass spectrometry imaging (MSI) of the localization of capsaicin in cross-sections of the capsicum fruits at a resolution of 250 Âµm using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. Post source decay of protonated capsaicin ion revealed structural information of the corresponding acid amide of vanillylamide and C9 chain fatty acid. MALDI-TOF-MSI confirmed that localization of capsaicin in the placenta is higher than that in the pericarp. In addition, it revealed no localization of capsaicin in seed and the higher localization of capsaicin at placenta surface compared with that in the internal region. A quantitative difference was detected between localizations of capsaicin at placenta, pericarp and seed in the capsicum fruits. This imaging approach is a promising technique for rapid quality evaluation general food as well as health food and identification of medicinal capsaicin in plant tissues.